A Research Journey ... The Longitudinal Study of Australian Children: Keynote Address for the Annual EarlyChildhood Services Conference - Harrison, L (My University, 2005)
This keynote presentation considers the research needs of child care workers, and how these may be served. In particular, it examines two new longitudinal studies, which take different approaches to studying child care and development. 'Growing up in Australia, the Longitudinal Study of Australian Children' follows two nationally representative samples of 500 preschool children and 5000 infants, to study how well children are doing on key developmental outcomes, and what affects their development. 'Child Care Choices' (CCC) is a collaborative project studying 600 families in metropolitan and regional New South Wales, which examines their childcare, preschool and school experiences.
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology